СОВРЕМЕННАЯ ТЕРАПИЯ ХРОНИЧЕСКОГО НАРУШЕНИЯ МОЗГОВОГО КРОВООБРАЩЕНИЯ. Часть 2 - А. А. Шмонин; В. С. Краснов; И. А. Шмонина; Е. В. Мельникова (SINAPS LLC, 2014)
Chronic cerebrovascular attack (CCVA) is a brain lesion caused by vascular factors. CCVA appears as cognitive impairments (CI), affective (emotional) disorders and focal syndromes. Treatment for CCVA requires a comprehensive approach. Combination effective therapy for CCVA involves secondary prevention of stroke and CI; treatment of CI; treatment of depression and other affective disorders; neuroprotective therapy. Basic therapy for CCVA includes modification of risk factors, antihypertensive, hypolipidemic, and antithrombotic therapies. Central acetylcholinesterase inhibitors (galantamine, rivastigmine, donepezil) and a reversible NMDA receptor blocker (memantine) are symptomatically used at a stage of vascular and mixed dementia. There are no unique guidelines for the therapy of mild and moderate vascular nondementia-related CI. Drug use, based on the neurochemical mechanisms underlying the development of vascular CI, is substantiated. When choosing psychotropic agents, it is necessary to take into account the causes and clinical manifestations of neuromediator deficiency. Antidepressants are used as essential drugs. Neuroleptics and tranquilizers are additionally administered in complex-pattern syndromes, such as depression with marked anxiety. Prescription of neuroprotectors may be effective in treating both stroke and CCVA. These medicaments are most effective when a damaging factor acts, i.e. neuroprotectors should be given in a risk situation and to reduce damage. Citicoline is one of the most test drugs in a group of neuroprotectors.